2021
DOI: 10.1016/j.jadohealth.2021.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Positive Youth Development Attributes on Posttraumatic Stress Disorder Symptoms Among Chinese Adolescents Under COVID-19

Abstract: This study examined the prevalence of posttraumatic stress disorder (PTSD) symptoms among adolescents in mainland China under COVID-19. The direct effects of the perceived threat of COVID-19 and positive youth development (PYD) qualities, as well as the moderating effect of PYD qualities on PTSD symptoms, were studied. Methods: Five schools in Chengdu, Sichuan, China, participated in this study. Two waves of data were collected before school lockdown (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 38 publications
8
72
0
Order By: Relevance
“…This result is in close agreement with those found for rapid systematic reviews and meta-analyses on the reported rates of PTSD among medical staff during the COVID-19 pandemic (43). However, this rate for PTSD was higher than those of the Chinese public (4.6%) one month after the COVID-19 outbreak in China ( 44) and a similar report on PTSD (10.4%) among Chinese adolescents in June 2020 (45). This comparison highlighted the importance of paying attention to the PTSD status quo of frontline medical workers in Wuhan during the fight against COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…This result is in close agreement with those found for rapid systematic reviews and meta-analyses on the reported rates of PTSD among medical staff during the COVID-19 pandemic (43). However, this rate for PTSD was higher than those of the Chinese public (4.6%) one month after the COVID-19 outbreak in China ( 44) and a similar report on PTSD (10.4%) among Chinese adolescents in June 2020 (45). This comparison highlighted the importance of paying attention to the PTSD status quo of frontline medical workers in Wuhan during the fight against COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research also found that emotional intelligence is a strong predictor of psychological disorders [ 13 ]. As emotional intelligence is an internal asset to show oneā€™s self-perceived emotional competency, it can be one of the positive youth development attributes [ 31 ]. A study highlighted the protective role of positive youth development attributes in protecting adolescents from depression in Chinese adolescents [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social support is believed to influence the individualsā€™ responses to stressful events as an individual external asset under COVID-19 [ 9 ]. There is a common proposition that the developmental assets are factors facilitating adolescent development, which means social support can be one of the positive youth development attributes [ 31 ]. The protective effect of possessing strong positive youth development qualities on adolescentsā€™ mental health in stressful situations verified the social support protective role [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of articles focused entirely on child and adolescent populations ā‰¤18 years of age. However, 24 studies also included populations ā‰„18 years (Alamrawy, Fadl, & Khaled, 2021;Banati, Jones, & Youssef, 2020;Buzzi et al, 2020;Chahal et al, 2021;Chen, She, et al, 2020;Commodari & La Rosa, 2020;Conte et al, 2020;de Matos et al, 2020;Esposito et al, 2020;Ferrando et al, 2020;Fish et al, 2020;Fitzpatrick, Carson, & Weisz, 2020;Janssen et al, 2020;Matovu, Kabwama, Ssekamatte, Ssenkusu, & Wanyenze, 2021;Munasinghe et al, 2020;Murata et al, 2021;Qi, Liu, et al, 2020;Rauschenberg et al, 2020;Scott et al, 2021;Shek et al, 2021;Storch et al, 2021;Tanaka & Okamoto, 2021;Tromans et al, 2020;. Thirteen studies targeted primary school populations (<12 years) (Alonso-Mart ınez et al, 2021; Chen, Chen, et al, 2020; de Avila et al, 2020;Dumas, Ellis, & Litt, 2020;Fontenelle-Tereshchuk, 2020;A.…”
Section: Age Distributionmentioning
confidence: 99%